The Dynamics of Europeanness of Lithuania’s Media Elite (2008–2015) - Matonytė, Irmina; Bernatavičiūtė, Gabrielė; Šumskas, Gintaras (Žurnalistikos tyrimai, 2017)
This article presents insights about Lithuania’s media elite, gained during research carried out on the basis of a complex Europeanness model, developed by Heinrich Best (Best 2012: 208-233). Data describing Lithuania’s media elite are analyzed with reference to three dimensions or facets, identified in the original model of Europeanness: emotive, cognitive-evaluative and projective-conative. However, the list of variables examined in the study is considerably longer as compared to the initial static model offered by Best, and the analysis is much more detailed. This comparative study is aimed at identifying and describing the evolution of emotive identification of Lithuania’s media elite with Europe in terms of the objective and judging approach of the EU in the period from 2008 to 2015. Results of the research revealed a clear trend that Lithuania’s media elite have been becoming European. It was noticed that it tends to increasingly associate itself emotionally with Europe. Besides, the number of representatives of this elite group that assesses the common EU governance negatively (when the EU’s common foreign policy in respect of countries found beyond the EU borders is becoming increasingly accepted) has been consistently decreasing and the trust in the EU institutions has been enhancing. Looking to the future, the representatives of Lithuania’s media elite tend to assess the EU prospects in the medium-term and long-term (10 years) optimistically. They also hold the view that 10 years later the EU, as a geopolitical, political and economic entity will be stronger, and that both social and economic differences among the EU member states will not be so sharp. Euroscepticism is seen not only on the cultural plane. Correlation analysis has revealed that young age (people under 40) and an intensive socialization in the EU networks (constant communication with the EU partners) determine that Lithuania’s media elite have been becoming European.
Keywords: Europeanness; media elite; the European Union; the EU institutions; Lithuania; emotive or affective identity; assessment; EU’s common foreign policy; trust; future prospects of the EU